HUBUNGAN KARAKTERISTIK PERAWAT DENGAN PENANGANAN AWAL PASIEN CEDERA KEPALA DI RUANGAN IGD - Vera Sesrianty (JURNAL KESEHATAN PERINTIS, 2017)
Ten leading causes of death in the world partly because of road accidents and is expected to be the three main causes of disability for life. ER as the main gateway handling emergency cases at the hospital plays an important role in saving the lives of patients, especially patients with injury head. The purpose of this study is d ike tahui relationship between the level of knowledge and the characteristics of the nurse with an initial treatment of head injury patients in the ER Hospital Dr. Achmad M o chtar London 2016. This study was done p No 11 s / d 20 July 2016, with respondents all nurses in the installation Emergency Hospital Dr. Achmad Mochtar Bukittinggi as many as 17 people. The research design was a descriptive analytic cross sectional approach. The statistical test used in this study is the Chi-square test. The results of this study showed that there is relationship between old nurse working with the initial handling of head injury patients, based statistically obtained p value = 0,020 (p≤0,05). There is no relationship between the status of nurses with initial handling of head injury patients, based statistically obtained p value = 0.105 (p> 0.05). It is expected that the results obtained from this study could provide further i nformation for researchers who want to conduct research related to the study that the results of the next study more valid and accurate and can use different variables or variable.